Web-Buzz Vision Consultation Application - Tang, Xin Zhe (2023)
Strabismus, often known as crossed eyes, is an eye misalignment. One of the most prevalent eye problems. Begun in 2019, the outbreak of coronavirus disease (COVID-19) caused significant disruption in all health sectors including the ophthalmology sector. People are compelled to postpone treatment because they are unable to attend or the clinic is overloaded. On the other hand, Due to the heavy workload of the patient record, most eye doctors did not manage the patient as well. Eye doctors use the traditional method to manually record the patient’s treatment. Hence, this system is proposed to overcome the current limitation of the web-buzz vision consultation application. As a reference for this project, some studies had been done to identify an existing platform, device, and even an appropriate and user-friendly interface. The survey method of data collecting is used to determine the project and design requirements of the proposed system. The system implements an agile methodology as it provides higher responsiveness and minimizes errors during development. The methodology consists of 6 phases which are requirement, design, development, test, deploy and review. First, project requirements and objectives are determined, followed by the system design and development. After the development phase, a UAT method is conducted to test the functionality, availability, performance and flexibility of the system. In a nutshell, this proposed system will be released and evaluated by users.